Antibodies against Pneumococcal Capsular Polysaccharides and Natural Anti-Galactosyl (Alpha-Gal) in Patients with Humoral Immunodeficiencies. (17th December 2017) - Kralickova, P.; Kuhnova, J.; Soucek, O.; Vodarek, P.; Zak, P.; Simkovic, M.; Motyckova, M.; Smolej, L.; Mala, E.; Andrys, C.; Krejsek, J.; Thon, V.
Abstract : Humoral deficiencies represent a broad group of disorders. The aim of the study was to compare the levels of antibodies against pneumococcal capsular polysaccharides (anti-PCP) and natural anti-galactosyl (anti-Gal) antibodies in (1) patients with chronic lymphocytic leukaemia (CLL), (2) patients with common variable immunodeficiency (CVID), and (3) a healthy population and to explore their diagnostic and prognostic potential. Serum immunoglobulin levels and levels of anti-Gal IgG, IgA, and IgM and anti-PCP IgG and IgG2 were determined in 59 CLL patients, 30 CVID patients, and 67 healthy controls. Levels of IgG, IgA, IgM, anti-Gal IgA, anti-Gal IgM, and anti-PCP IgA were lower in CLL and CVID patients than in healthy controls (p value for all parameters < 0.0001). Decrease in the levels of IgA, IgM, anti-Gal IgA, and anti-PCP IgA was less pronounced in the CLL group than in the CVID group. IgA decline, anti-Gal IgA, anti-PCP IgA, and anti-PCP IgG2 were negatively correlated with CLL stage. We devise the evaluation of anti-Gal antibodies to be a routine test in humoral immunodeficiency diagnostics, even in cases of immunoglobulin substitution therapy. Significant reductions, mainly in anti-Gal IgA, IgM, and anti-PCP IgA levels, may have prognostic importance in CLL patients.